Landscape and predictions of inflammatory bowel disease in China: China will enter the Compounding Prevalence stage around 2030 - Shao, Bule; Yang, Wenjing; Cao, Qian (Frontiers in Public Health, 2022)
Background This study aims to explore the epidemiological trends of inflammatory bowel disease (IBD) over the past three decades in China and further predict the trends of IBD in the next 25 years. Methods The prevalence, incidence, mortality, years of life lived with disability (YLDs), years of life lost (YLLs), disability-adjusted life years (DALYs), and annual percentage changes of the above metrics of IBD in China from 1990 to 2019 were extracted from the Global Burden of Disease Study 2019. The corresponding trends in the next 25 years were predicted. Results From 1990 to 2019, the cases of IBD in China raised to 484 thousand [95% uncertainty interval (UI) 411–571] and 427 thousand (366–498) among males and females, respectively. The age-standardized incidence rate of IBD increased from 1.72 per 100,000 population (1.44–2.05) to 3.35 per 100,000 population (2.88–3.88) among males and from 1.20 per 100,000 population (1.02–1.42) to 2.65 per 100,000 population (2.29–3.08) among females. The highest incidence rate occurred in people aged 35–39 years. The total YLDs attributed to IBD significantly increased, but the YLLs showed a decreasing trend, resulting in minor alterations of the DALYs. In the next 25 years, the incidence of IBD would continue to increase until a plateau by 2030, and IBD-related deaths would also increase to about 7.57 thousand by 2044 despite the decreasing age-standardized mortality rate. Similar trends were observed for both sexes, with a slight male predominance. Conclusions Although China is still a low-endemic area of IBD, the prevalence and incidence of IBD dramatically increased in the past three decades. The burden of IBD in China is expected to grow continuously in the next 25 years due to the large population base and severe aging problem. China is estimated to enter the Compounding Prevalence stage around 2030.